UPAYA MENINGKATKAN KREATIVITAS SISWA MELALUI MODEL PROJECT BASED LEARNING - Fitri Agustina Lubis (Universitas Muhammadiyah Tapanuli Selatan, 2018)
This research aims to improve the management of creativity and learning biology learning model through the application of Project Based Learning (the execution) on the subject of environmental pollution in the class X MIA-1 SMA Negeri 1 Sipirok TP 2017/2018. This type of research this is a class action research (PTK) using two cycles of learning. Data collection techniques used are tests and observations with data collection tool berupalembar test of creativity and learning management of biological observation sheets. Based on the results of research conducted, the test results obtained in cycle I, with a total value of 2299, the value of the average number of students who complete 71.84 as many as 9 people (71.87%) and cycle II obtained total value of 2995 with average number of 93.59 students who complete 30 people (93.75%) so that the cycle of I to II an increase in cycle 7 (21.88%). As for the observations against the management of the biological cycle of learning I obtained an average percentage of 70% and on Siculus II becomes 91%. Thus, from cycle to cycle I II occur an increase of 21% from kulaifikasi simply be good criteria. The study was finalized in cycle II because the indicators of success have been achieved and meets the criteria of ketuntasan so that the conclusions of this research is that learning through Project Based Learning (the execution), it can increase creativity and learning areas of biology on the subject of environmental pollution in the class X MIA-1 SMA Negeri 1 Sipirok TP 2017/2018.